Benign Yet Alarming: Cystitis Glandularis and Cystica with Gross Hematuria : A Case Report - Rinaldi, Randhi; Tobing, Edwin; Tansol, Christiano; Kristiani, Erna (Journal of Neonatal Surgery, 2025)
Introduction: Cystitis glandularis and cystitis cystica are benign proliferative conditions of the bladder mucosa, often arising as a reactive response to chronic irritation or inflammation. While frequently asymptomatic, they can occasionally present with alarming symptoms such as gross hematuria and urinary retention, mimicking malignancy. Case Presentation: We report the case of a 43-year-old uncircumcised male who presented with acute urinary retention and gross hematuria due to intravesical blood clots. Physical examination revealed suprapubic fullness and a mildly enlarged prostate. A three-way Foley catheter with manual irrigation was required for decompression. Cystoscopic examination showed multiple raised mucosal lesions and pseudopolyps with active bleeding in the posterior bladder wall. Histopathological analysis of the bladder biopsy confirmed the diagnosis of cystitis glandularis and cystitis cystica. The patient was managed conservatively with non-steroidal anti-inflammatory drugs (NSAIDs), bladder irrigation, and increased hydration. Conclusion: Although benign, cystitis glandularis and cystitis cystica can present with severe urological symptoms such as hematuria with clot retention. Prompt evaluation with cystoscopy and biopsy is essential to exclude malignancy. Conservative management is often effective, but ongoing surveillance is recommended due to the potential for recurrence and the rare risk of malignant transformation.